Computational fluid dynamics investigation on the irrigation of a real root canal with a side-vented needle - Mingzhou Yu; Yi Li; Mengdie Zhao; Zhengqiu Huang; Na Zhou; Hanhui Jin (BMC, 2024)
Abstract Background Root canal therapy is one of the main treatments for root canal diseases, and effective irrigation is the key to successful treatment. Side-vented needle is one of the commonly used needle types in clinic. In the real root canal, due to the influence of the curvature of the root canal, the irrigation flow field in different needle directions shows obvious differences. At the same time, changes in root canal curvature and working depth will lead to changes in irrigation efficiency and the flow field. Both the mainstream of the irrigation flow and the shear stress near the wall changes significant. Consequently, either the replacement in the root canal or the removal efficiency of the smear layers is apparently modified. Materials and methods In this paper, the permanent root canal of the maxillary first molar prepared until 15/04 were scanned by micro-CT, and then imported into the software for 3D reconstruction. The key parameters of flushing efficiency of 30G side needle at different working depths of 4.75 mm, 5 mm, 5.25 mm and 5.5 mm were compared. Meanwhile, the simulated models with different curvatures of 0°, 5°, 10°, 20° and 30° based on the real root canal were reconstructed to investigate the curvature effect on the irrigation efficiency. Results The results show that moderate working depth (such as 4.75 mm and 5.25 mm in present paper) helps to improve the replacement capacity of irrigation flow. At the same time, the apical pressure decreased as the working depth increased. The curvature of the root canal seriously affects the removal depth of the smear layers of the root canal. A root canal with a large curvature (especially 20° and 30°) can significantly improve the difficulty of irrigation. Conclusions (1) Moderate working depth helps to improve the displacement capacity, the ERD of the irrigation flow is generally improved at the working depths of 4.75 mm and 5.25 mm, and the apical pressure will decrease with the increase of working depth. (2) The large curvature of the root canal can significantly improve the difficulty of irrigation. The curvature of the root canal can severely influence the removal depth of the smear layer on the wall. It can be found both the span and the depth of the ESS for little curvatures (5° and 10°) root canals are higher than those for large curvatures (20° and 30°).